CFD Modelling of Blast Waves from BLEVEs - Roald Hansen Olav; Malte Kjellander (Chemical Engineering Transactions, 2016)
Boiling Liquid Expanding Vapour Explosions (BLEVEs) are among the major hazard scenarios to be considered in siting studies as well as transportation safety assessments. The main hazards from BLEVEs consist of blast waves and projectiles, and radiation for flammable and toxicity for toxic substances. Well established relations exist to predict consequences for BLEVEs in the open. With increasing confinement, due to tanks being inside or surrounded by buildings, or tunnels for transport scenarios, the consequences from blast waves become more severe, while the empirical relations can no longer be used to predict the consequences. Blast waves from BLEVEs are partly caused by expansion of pressurized vapour head, partly by the rapid phase change of the boiling liquid, and further pressure waves may be generated by pressure oscillations and combustion. Which mechanism that will dominate the blast generation will depend on the vapour head volume and pressure and the degree of superheat of the liquid. FLACS, a computational fluid dynamics (CFD) model has been applied to model blast waves from BLEVEs. The modelling of the different contributions to blast waves has been validated against experiments. For accurate results, both directional effects due to shape of tank and the cooling during the rapid phase change must be included in the modelling. With the validated modeling approach the CFD model can be applied to predict partially confined BLEVE scenarios, including tunnel scenarios. We consider our modelling approach to be more accurate than similar work published in the past.